Modulation of the central nervous system immune response and neuroinflammation via Wnt signaling in health and neurodegenerative diseases - Kevin Fang (Ibrain)
Abstract The immune response in the central nervous system (CNS) is a highly specialized and tightly regulated process essential for maintaining neural health and protecting against pathogens and injuries. The primary immune cells within the CNS include microglia, astrocytes, T cells, and B cells. They work together, continuously monitor the CNS environment for signs of infection, injury, or disease, and respond by phagocytosing debris, releasing cytokines, and recruiting other immune cells. In addition to providing neuroprotection, these immune responses must be carefully balanced to prevent excessive inflammation that can lead to neuronal damage and contribute to neurodegenerative diseases. Dysregulated immune responses in the CNS are implicated in various neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis. Wnt signaling is a crucial pathway in the CNS that regulates various cellular processes critical for brain development, function, and maintenance. Despite enhancing immune responses in the health CNS, dysregulated Wnt signaling exacerbates neuroinflammation in the neurodegenerative brains. This review summarized the role of Wnt signaling in regulating immune response under different conditions. We then examined the role of immune response in healthy brains and during the development of neurodegenerative diseases. We also discussed therapeutic intervention in various neurodegenerative diseases through the modulation of the Wnt signaling pathway and neuroinflammation and highlighted challenges and limitations in current clinical trials.